Enhancing CBT Consultation With Multicultural Counseling Principles. Issue 4 (November 2022) - Calloway, Amber; Creed, Torrey A.
Highlights: Therapy delivered in a culturally responsive way can lead to better outcomes. Consultation is of critical importance in clinical skill development. Multicultural counseling principles can be integrated into all aspects of training. Abstract: The use of multicultural principles to enhance cognitive behavioral therapy (CBT) for individuals of marginalized backgrounds has received increased attention in light of the heightened national awareness of systemic oppression and racialized violence directed towards Black, Indigenous, and People of Color. However, there has been less of a focus on applying such principles to consultation for skill development. If ethical guidelines are expected to influence the behavior of clinicians in session, guidance is needed to indicate how and where and when clinicians should receive training in implementing culturally responsive CBT. Individual reading and reflection are necessary but are not sufficient in acquiring new clinical skills. Consultation is recommended and strongly suggested when clinicians are working with new populations or delivering a new treatment, or even using a new modality. Consultation can also be useful when adopting a new approach or stance to therapy. For practicing clinicians who have not developed these skills, additional consultation can and should be used to address this gap. Moving forward, integration of cultural responsiveness into standard consultation will ensure that these skills are seen as a core competency, rather than an optional additional skill that may be (or not be) elected. This paper presents core experiences that may be integral to a CBT consultation model that aims to enhance providers' ability to provide CBT in a way that is culturally responsive to their clients. These recommendations attend to both content and process within CBT consultation and reflect guiding assumptions for helping clinicians to develop the ability to practice CBT in a culturally responsive manner, including (a) normalizing discussions of cultural identity and oppression, (b) an emphasis on cultural self-awareness, (c) emphasizing culturally informed CBT case conceptualization, and (d) skill development in applying cultural elements to CBT interventions.